Expression and activity of the Toll-like receptor family in the term and preterm human placenta. - Shalini Patni (2007)
Toll like receptors (TLR) have emerged as key upstream mediators of inflammation at many tissue sites in humans. Parturition is considered an inflammatory process so it was hypothesised that TLR activity within gestation-associated tissues, such as the placenta, might have an important role in the initiation and/or maintenance of normal term labour and in various pathological states of pregnancy such as infection associated preterm labour.Expression of transcripts for TLR1-10 was confirmed in term (>37 weeks of gestation) human placentas collected in the absence of labour (elective caesarean sections, termnon-laboured) and after the completion of labour at term (normal vaginal delivery, termlaboured,) and preterm ( <37 weeks gestation, preterm delivery). Explants of placental tissue were cultured in vitro in the presence of ligands for TLR 1-9 (an agonist of TLR 10 has not yet been identified). Cytokine (TNFa, IL-6, IL-8 & IL-10) production into the culture supernatants was then measured using ELISA.Reactivity to all agonists except CpG oligonucleotides was observed in all the three groups studied indicating that, other than TLR9, all of the receptors studied yielded functional responses. Placentas collected after the completion of labour (term laboured; n=17) had significantly more LPS (TLR4 agonist) and R848 (TLR7/8) agonist induced TNFa than those obtained in the absence of labour (term non-laboured", n=17). In contrast, gene expression analysis revealed that transcripts for TLR2 and TLR5 only were significantly elevated in association with labour. These findings indicate that there is no relationship between changes in mRNA expression and function of these receptors within the placenta.The study of placentas collected following preterm spontaneous vaginal delivery (preterm svd\ n=10) compared with those obtained after term laboured (n=17) revealed that significantly less TNFa and IL-6 were produced by placentas following preterm delivery in response to all TLR agonists. In contrast, the expression of TLR transcripts was found not to be statistically different for any of the TLRsl-10 in these two groups.Thus the human term placenta expresses a variety of functional TLRs and whilst LPS and R848 mediated TNFa increase at term labour, more detailed analysis of contributing cell types and signalling molecules is required to elucidate the role of this family of receptors in parturition.